PENGARUH PEMBERIAN REWARD MELALUI PENGGUNAAN TABUNGAN BINTANG TERHADAP PENINGKATAN MOTIVASI BELAJAR ANAK USIA 5-6 TAHUN DI RA NURUL HUDA BURUJUL PARUNGPONTENG - Fuadah, Samrotul; Sidiq, Hamid; Muthmainah, Ai Siti (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2023)
This study aims to examine the effect of rewards through the use of "star savings" on increasing learning motivation in children aged 5-6 years at RA Nurul Huda Burujul Parungponteng, Tasikmalaya Regency. The research used a quantitative descriptive method with pretest and posttest as measurement tools. The pretest results showed that 52.9% of students had not yet developed, 35.3% experienced improvement, and 11.77% were performing as expected, although none had shown excellent development. After the intervention of rewards through star savings, the posttest results indicated a significant increase in learning motivation, with 52.9% of students achieving satisfactory results and 47.1% reaching excellent results. These findings confirm that providing rewards through star savings significantly improves both learning motivation and learning outcomes. This study demonstrates that the reward approach is effective in encouraging learning motivation in early childhood.